Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1074/jbc.271.45.28458
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transcription Factor Induction in Retinal Pigment Epithelial Cells during Photoreceptor Phagocytosis

Abstract: Expression of early response genes during rod outer segment phagocytosis by normal Long Evans and Royal College of Surgeons-rdy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The molecular mechanism of RPE phagocytosis remains largely unclear, but appears to be OS specific, at least at the level of the initial events of recognition, binding, and internalization. Numerous studies in RCS rats have suggested that the RPE utilizes distinct mechanisms for uptake of OS and latex microspheres [7][8][9][10]. The c-mer receptor tyrosine RPE cell culture Primary cultures of human RPE cells (hRPE) were a gift from Dr. J. Burke (Medical College of Wisconsin, Wis.), and were obtained as confluent cell monolayers at early passages ranging from 3 to 8.…”
mentioning
confidence: 99%
“…The molecular mechanism of RPE phagocytosis remains largely unclear, but appears to be OS specific, at least at the level of the initial events of recognition, binding, and internalization. Numerous studies in RCS rats have suggested that the RPE utilizes distinct mechanisms for uptake of OS and latex microspheres [7][8][9][10]. The c-mer receptor tyrosine RPE cell culture Primary cultures of human RPE cells (hRPE) were a gift from Dr. J. Burke (Medical College of Wisconsin, Wis.), and were obtained as confluent cell monolayers at early passages ranging from 3 to 8.…”
mentioning
confidence: 99%
“…Ershov and co-workers [12] have shown that the expression of the transcription factors AP-1 and AP-2 is increased in RPE cells after ROS phagocytosis. These transcription factors may then bind the tyrosinase gene promoter at their corresponding binding sites [13] and thereby upregulate transcription of tyrosinase.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in NPD1 was almost six times higher than that of RPE cells exposed to microspheres. Outer segment phagocytosis also triggered early response gene induction [21], as well as COX-2 [22] and PPARγ [23] expression.…”
Section: Photoreceptor Outer Segment Phagocytosis Selectively Attenuamentioning
confidence: 97%